Brazilian women, invisible workers: the experiences of women street vendors in Brazil - Siqueira, Adryanna Alves De (Kansas State University, 2008)
This study focuses on experiences of women workers in Brazilian street markets, as told in their own words. Feminist epistemology informs this study, including face-to-face interviews as well as participant observation. Participants share how they became informal entrepreneurs, offering a unique perspective of market work that is local and personal. Two major concepts inform this study. First, local gender regimes emphasizes context as influential in women's practices and perceptions; both opportunity structures and cultural milieux restrain earning potential. Equally important is the second concept, luta, or "fighting energy," a concept that emerged from interviews. Luta expresses agency that guided these women toward an entrepreneurial decision. Interviews reveal that traditional expectations, conducive to acceptance of gendered experiences for these women's mothers and grandmothers, were transformed into new meaning in the marketplace. However, they do not openly deny dominant ideological practices. In a process that includes both resistance and accommodation, they maintain their business, but keep religious ideologies of obedience and responsibility for household tasks. These ideologies, mostly unacknowledged, may keep some of them as feirantes –market vendors who see themselves and their business as limited. To others, the street becomes a preparatory stage to engage in larger business endeavors; they become empreendedoras informais, who demonstrate an entrepreneurial vision to take the business beyond a small market stall. Findings support the feminist postulate that gendered structural factors significantly shape experiences of women, but also that a strong element of agency marks practices of Brazilian women in the marketplace. In particular, this study contributes to an international scholarship by and for women, exploring cultural influences on their life processes and perceptions. Literature on women and the informal economy should continue to include the pervasiveness of gendered ideologies without neglect to women's capacity for producing change through human agency.
Keywords: Informal economy; Informal markets; Women street vendors; Luta; Sociology, General (0626)